On the impact of improved dosimetric accuracy on head and neck high dose rate brachytherapy. Issue 1 (July 2016) - Peppa, Vasiliki; Pappas, Eleftherios; Major, Tibor; Takácsi-Nagy, Zoltán; Pantelis, Evaggelos; Papagiannis, Panagiotis
Abstract: Purpose: To study the effect of finite patient dimensions and tissue heterogeneities in head and neck high dose rate brachytherapy. Methods and materials: The current practice of TG-43 dosimetry was compared to patient specific dosimetry obtained using Monte Carlo simulation for a sample of 22 patient plans. The dose distributions were compared in terms of percentage dose differences as well as differences in dose volume histogram and radiobiological indices for the target and organs at risk (mandible, parotids, skin, and spinal cord). Results: Noticeable percentage differences exist between TG-43 and patient specific dosimetry, mainly at low dose points. Expressed as fractions of the planning aim dose, percentage differences are within 2% with a general TG-43 overestimation except for the spine. These differences are consistent resulting in statistically significant differences of dose volume histogram and radiobiology indices. Absolute differences of these indices are however small to warrant clinical importance in terms of tumor control or complication probabilities. Conclusions: The introduction of dosimetry methods characterized by improved accuracy is a valuable advancement. It does not appear however to influence dose prescription or call for amendment of clinical recommendations for the mobile tongue, base of tongue, and floor of mouth patient cohort of this study.